O efeito da transparência sobre a liquidez do mercado secundário de debêntures no Brasil - Paula, Anderson Luiz Pereira de (2016)
The liquidity of the secondary market of corporate bonds has been the subject of a wide debate by several players in the Brazilian capital market – either by investors, who are looking for a better way to identify and price the cost to discard a position, or by companies that seek alternatives to reduce the cost of debt, or by regulators, who seek to encourage the financing of companies through the capital market, promoting financial disintermediation. Using a complete database of bonds transactions in the Brazilian secondary market and econometric models for panel data analysis (longitudinal), this work presents the effect caused by the implementation of the Brazilian Single Price Registration System (REUNE) in the liquidity of the secondary market of bonds between January 2010 and December 2015. Results suggest that investors have become able to getting better deals or even get vaccinated against bad managers and fraudulent operations, a typical situation in resource management of pension funds. This paper seeks to contribute to the literature by providing new evidence that increased transparency in secondary market transactions is an important determinant of better business for investors in the capital market.